Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3847/0067-0049/226/1/4
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Stellar Elemental Abundance Techniques and Measurements

Abstract: Stellar elemental abundances are important for understanding the fundamental properties of a star or stellar group, such as age and evolutionary history, as well as the composition of an orbiting planet. However, as abundance measurement techniques have progressed, there has been little standardization between individual methods and their comparisons. As a result, different stellar abundance procedures determine measurements that vary beyond quoted error for the same elements within the same stars (Hinkel et a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(103 citation statements)
references
References 144 publications
4
96
0
Order By: Relevance
“…Since the last update published in Hinkel et al (2016), we have included 55 additional catalogs from the literature as well as 11 new elements and species (namely: Si II, Nb II, Pr II, Gd II, Tb II, Dy II, Er II, Tm II, Yb II, Hf II, Th II), as shown in Fig. 2.…”
Section: The Hypatia Catalog 21mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the last update published in Hinkel et al (2016), we have included 55 additional catalogs from the literature as well as 11 new elements and species (namely: Si II, Nb II, Pr II, Gd II, Tb II, Dy II, Er II, Tm II, Yb II, Hf II, Th II), as shown in Fig. 2.…”
Section: The Hypatia Catalog 21mentioning
confidence: 99%
“…Please see Hinkel et al (2014Hinkel et al ( , 2016 for more details. In the header, "S/N" is signal-to-noise report by the literature source, "λ Range" is the wavelength coverage, "Stellar Atmo" is the stellar atmospheric model, "Eq.…”
Section: Atlas9mentioning
confidence: 99%
“…Multiple surveys studied the distribution of the stellar population C/O ratios (Teske et al 2014;Nissen et al 2014;Hinkel et al 2016;Brewer & Fischer 2016). These works concluded that planets hosting stars C/O ratios cluster around the solar (0.55) value, and very few stars (if any) have C/O larger than 0.8.…”
Section: Case: High Stellar C/o Ratiomentioning
confidence: 99%
“…It would thus be expected that each ion of each element would also be affected to different degrees. For a broader view of uncertainties in spectroscopic abundance determination we refer the interested reader to the detailed empirical study of Hinkel et al (2016).…”
Section: Summary Of Uncertaintiesmentioning
confidence: 99%